Studies on structural, optical, and photoelectric properties of CdS1–xSex films fabricated by selenization of chemical bath deposited CdS films. Issue 2 (22nd November 2016) - Lu, Tianyu; Gu, Han; Ge, Zhenhua; Zhang, Lei; Wu, Wangping; Wang, Zhicheng; Fang, Yong; Han, Zhida; Qian, Bin; Jiang, Xuefan
Abstract : In this paper, high‐photosensitive CdS1– x Se x films are synthesized by a two‐step technique, which includes the chemical bath deposition of CdS films and a following selenization process. The structural, optical, and photoelectric properties of the CdS1– x Se x films were investigated. With the substitution of selenium for sulfur atoms, grain sizes of the as‐prepared CdS1– x Se x films are effectively enlarged and reach the scales of the films thickness when the selenization temperature exceeds 450 °C. With increasing the selenization temperature from 350 to 550 °C, the band gaps of CdS1– x Se x films gradually decrease from 2.37 to 1.82 eV. Under the co‐action of the grain‐size enlargement and band‐gap decrease, the CdS1– x Se x films fabricated at 450 °C show very pronounced photosensitivity. Noteworthy, the ratio of photo to dark conductivity of the CdS1– x Se x film selenized at 450 °C reaches 1.1 × 10 5, suggesting a promising application potential in the photoelectric devices.